MAKNA VERBA MAJEMUK ~KIRU DALAM BAHASA JEPANG Kajian Struktur dan Semantis - Taqdir Taqdir (IZUMI, 2014)
Abstract  The purpose of this paper is to know the structure of compound verb (V + V) in Japanese. The structure is a forming of zenkoudoushi (first verb) and koukoudoushi (second verb). The second verb is kiru. And the first verbs are joutai doushi (statis) keizoukudoushi (contuinity), shunkandoushi (fungtual), and daiyoushudoushi (the four verb). This classification from the Kindaichi’s classification. As a single verb kiru means to cut, to slice, to decide, and to turn off. When it combined with other verbs, the verb kiru will form a compound verb which has several meanings. Commonly, compound verb kiru has two meanings, namely in terms of lexical meaning and syntactical meaning. Lexically, compound verb kiru means setsudan ‘cutting’ and shuketsu ‘ends/over’, while syntactically this verb means kyokudo ‘extraordinary/ infinite’ and kansui ‘perfective’. The compound verb ~kiru which attached to continuity (keizokudoushi) has meaning as setsudan ‘cutting’, shuketsu ‘ends/over’, and kansui ‘perfective’, while when it is attached to the punctual verb (shuunkandoushi) means kyokudo ‘extraordinary/ infinite’.  Keyword : zenkoudoushi, koukoudoushi, compound verb, ~kiru